3D Microstructure Reconstruction of Bamboo Fiber and Parenchyma Cell. Issue 8 (3rd August 2021) - Wu, Wenwang; Xia, Re
ABSTRACT: Synchrotron radiation absorption based and phase-contrast X-ray tomographic microscopy techniques are applied for observation and identification of the 3D features of bamboo fiber and parenchyma cells at micro-scale. The results revealed the 3D features within the fiber-reinforced bamboo. As to the 3D microstructure, the fiber and the parenchyma cells matrix are reconstructed, respectively. The 3D reconstruction will reveal necessary 3D geometrical and material parameters for better understanding the mechanical and biological functions of bamboo and provide new research ideas for relevant mechanism and the design of hierarchical structure of composite material.